TAX KNOWLEDGE AND TAX COMPLIANCE OF MICRO AND SMALL ENTERPRISES IN GOMBE STATE, NIGERIA: MODERATING EFFECT OF RECORD KEEPING PRACTICE - Bello, Umar; Bayu, Umar Faruk; Adamu, Nuhu Saidu; Ogboji, Ogboji Abraham; Abubakar, Muhammad Abdul; Lass, Ruth; Usman, Abubakar; John, Jandiya (Kashere Journal of Management Sciences, 2024)
Tax income is undoubtedly one of the major sources of revenue of most countries, hence tax compliance is one of the troubling issue faced by tax authorities. Therefore this study evaluated the moderating effect of record keeping practice on the relationship between tax knowledge and tax compliance behaviour of Micro and Small Enterprises (MSE) in Gombe state Nigeria. The study employed web based method of data collection where 360 responses were retrieved from the online questionnaire distributed to the entire 480 MSEs registered with Small and Medium Enterprises Development Agency (SMEDAN) and corporate Affairs Commission (CAC) in Gombe state Nigeria. Partial Least Squared-Structural Equation Modelling (SmartPLS3) was employed to analyse the data. The study found out that tax knowledge has a significant positive effect on tax compliance behaviour in MSEs in Gombe state-Nigeria. Similarly, record keeping practice was found to moderate the relationship between tax knowledge and tax compliance behaviour of MSEs. Hence, the study recommends that tax authorities to put more effort in the provision of sensitization program that can boost MSEs record keeping practice and tax knowledge as well